1995
DOI: 10.1063/1.470118
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence of rotational relaxation of supercritical CF3H

Abstract: Polarized and depolarized Raman scattering measurement and molecular dynamics (MD) calculations have been performed for supercritical CF3H at various densities along an isotherm higher than Tc by about 6 K in order to investigate the density dependence of rotational relaxation. The rotational autocorrelation functions obtained from both methods, which are in satisfactory agreement with each other, showed liquid-like diffusional decay for the fluid at densities higher than ρc. The function changed in shape cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 40 publications
4
34
0
1
Order By: Relevance
“…Recent Raman scattering studies of pure supercritical fluids have shown that the form of the rotational correlation function depends on density. [10,11] In these studies the calculated rotational relaxation times had values of less than 1 picosecond which is comparable to the inverse of the collision frequency at low density. As the density increases the rotational correlation functions of the pure solvents exhibit a transition from free rotor to diffusive behavior.…”
Section: Rotationalmentioning
confidence: 73%
“…Recent Raman scattering studies of pure supercritical fluids have shown that the form of the rotational correlation function depends on density. [10,11] In these studies the calculated rotational relaxation times had values of less than 1 picosecond which is comparable to the inverse of the collision frequency at low density. As the density increases the rotational correlation functions of the pure solvents exhibit a transition from free rotor to diffusive behavior.…”
Section: Rotationalmentioning
confidence: 73%
“…In CF 3 H at low reduced densities, we observed an additional shoulder at ∼535 nm ( Figure 1, lower panel). This shoulder corresponds to a shift of ∼3000 cm -1 from the excitation wavelength (458 nm) and we conclude that it is due to Raman scatter from the ν 1 symmetric stretching mode of CF 3 H. 60 The steady-state behavior in supercritical fluids can be summed up as follows. Fluid density has little influence on the emission characteristics of BTBP in either supercritical CF 3 H or CO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…In addition, it was observed from a Raman spectroscopic study by Okazaki et al that the inversion is evident below half the critical density for supercritical CF 3 H ͑the fact that CF 3 H involves a weaker intermolecular interaction than water is reflected in the higher inversion density͒. 66 Thus, the apparent disagreement is present in the density dependence between the results from the NMR and simulations and those from Okada et al's dielectric relaxation measurements performed in the frequency range up to 40 GHz.…”
Section: Resultsmentioning
confidence: 99%